The effect of working capital management on firms’ profitability : comparative study on Middle East and West Europe companies - Husaria, Mhd Anas (2015)
This thesis investigates the relationship between working capital management and profitability of firms in the Middle East and Europe. This study used a sample of 54 firms listed in the Middle East and West Europe for the period of 2012-2013. The aim of this research is to test the effect of working capital management in the form of cash conversion cycle measurements on the profitability of firms in the Middle East and Europe. The results of this study revealed that there is no statistically significant relationship between cash conversion cycle measurements and profitability of firms measured as Return on Asset. Moreover, managers should use other tools and strategies to improve their firm’s profitability rather than managing the working capital efficiently.